Curcumin Alleviates Diabetic Retinopathy in Experimental Diabetic Rats - Yang, Fang; Yu, Jinqiang; Ke, Feng; Lan, Mei; Li, Dekun; Tan, Ke; Ling, Jiaojiao; Wang, Ying; Wu, Kaili; Li, Dai (Ophthalmic research, 2018)
To investigate the potential protective effects of curcumin on the retina in diabetic rats. An experimental diabetic rat model was induced by a low dose of streptozotocin combined with a high-energy diet. Rats which had blood glucose levels ≥11.6 mmol/L were used as diabetic rats. The diabetic rats were randomly divided into 3 groups: diabetic rats with no treatment (DM), diabetic rats treated with 100 mg/kg curcumin (DM + Cur 100 mg/kg), and diabetic rats treated with 200 mg/kg curcumin (DM + Cur 200 mg/kg). Curcumin was orally administered daily for 16 weeks. After 16 weeks of administration, the rats were euthanized, and eyes were dissected. Retinal histology was examined, and the thickness of the retina was measured. Ultrastructural changes of retinal ganglion cells, inner layer cells, retinal capillary, and membranous disks were observed by electron microscopy. Malondialdehyde, superoxide dismutase, and total antioxidant capacity were measured by ELISA. Expression levels of vascular endothelial growth factor (VEGF) in retina tissues were examined by immunohistochemical staining and ELISA. Expression levels of Bax and Bcl-2 in retina tissues were determined by immunohistochemical staining and Western blotting. Curcumin reduced the blood glucose levels of diabetic rats and decreased diabetes-induced body weight loss. Curcumin prevented attenuation of the retina in diabetic rats and ameliorated diabetes-induced ultrastructure changes of the retina, including thinning of the retina, apoptosis of the retinal ganglion cells and inner nuclear layer cells, thickening of retinal capillary basement membrane and disturbance of photoreceptor cell membranous disks. We also found that curcumin has a strong antioxidative ability in the retina of diabetic rats. It was observed that curcumin attenuated the expression of VEGF in the retina of diabetic rats. We also discovered that curcumin had an antiapoptotic effect by upregulating the expression of Bcl-2 and downregulating the expression of Bax in the retina of diabetic rats. Taken together, these results suggest that curcumin may have great therapeutic potential in the treatment of diabetic retinopathy which could be attributed to the hypoglycemic, antioxidant, VEGF-downregulating and neuroprotection properties of curcumin.